PETA DISTRIBUSI FREKUENSI KASUS TB PARU DI PUSKESMAS PURWOYOSO TAHUN 2017-2018 - Ima Afisatulia Solikhah; Fitria Wulandari (Dian Nuswantoro Semarang, 2020)
Indonesia is still a high burden countries (HBC) based on 3 indicators, namely pulmonary TB / TB/HIV, and MDR-TB. The number of TB cases in Indonesia 2017 was 420,994 cases, 63 people died because of TB in Semarang, Purwoyoso Primary Healthcare is one of the healthcare center in Semarang that had not used GIS (Geographic Information Systems)-based reporting. This research is a descriptive study. The object of this study was the medical record of patients with pulmonary TB cases and pulmonary TB case reports in Purwoyoso Primary Healthcare. Mapping of pulmonary TB cases was made with MapInfo. The design of the Geographic Information System with the MapInfo application presents a report on pulmonary TB cases at Purwoyoso Primary Healthcare. Based on the comparison of the number of pulmonary TB cases in the Purwoyoso Primary Healthcare region between 2016-2017 and 2017-2018, the number of pulmonary TB cases decreased in Kelurahan Purwoyoso, Pulmonary TB cases in Kelurahan Purwoyoso decreased by 6%, from 53% cases in 2015 -2016 to 47% cases in 2017-2018, while cases of Pulmonary TB in Kelurahan Kalipancur increased from 25% cases in 2015-2016 to 75% cases in 2017-2018. Purwoyoso Primary Healthcare should use a geographic information system so that the reporting process can be more effective.Keywords: Pulmonary TB, Geographic Information System, Purwoyoso Primary Healthcare